Greenland ship "Gustav Holm" at Scoresby Sund 1930 : Grønlandsskibet "Gustav Holm" ved Scoresby Sund 1930 - Petersen, Sofie (University of Southern California Digital Library (USC.DL), 2015)
Greenland ship "Gustav Holm" at Scoresby Sund 1930